The last instar larva and pupa of Ora depressa (Coleoptera: Scirtidae), a marsh beetle with underwater pupation - Libonatti, María Laura (2018)
In this contribution we describe and illustrate for the first time, detailed morphology and chaetotaxy of the last instar larva and the pupa of Ora depressa (Fabricius, 1801), and provide diagnostic characters and information on its biology. The last instar larva of O. depressa exhibits the characters traditionally recognized as diagnostic of the genus, i.e. the tip of the mandible obtuse, and the fourth maxillary palpomere long, almost as long as third palpomere. Ora depressa is characterized by a broadly elliptical body, which is widest at the metanotum, being brownish testaceous in color with several brown spots, having the dorsal surface mostly covered with numerous grooved scale-like setae and also several ungrooved scale-like setae, hair-like setae, club-like setae and pore-like sensilla distributed in a specific pattern, and the femur and tibiotarsus bearing a row of natatorial setae. The last instar larva of Ora depressa can be distinguished from those of the other known species of the genus by lobes of clypeolabrum being as long as wide and socket bristles with 2–6 inner teeth. The pupa of O. depressa differs from those of the other known species of the genus in the absence of pronotal horns and by the place where pupation occurs. Ora depressa pupates underwater, hanging from water’s surface with the aid of the laterally expanded pronotum which bears hydrophobic setation along the lateral margins.